The Phase Transition Model for Heat-Shrinkable Thermo-Sensitive Hydrogels Based on Interaction Energy (Communications in Computational Physics, 2020)
A biphase mixture continuum mechanics model is derived for neutral heat-shrinkablethermo-sensitive hydrogels in this paper. The mixing free energy of thespecial mixture is recalculated based on the partition function of Bose system, and itevaluates the contribution of the hydrophilic, hydrophobic interaction and hydrogenbonding to the volume phase transition behaviors. The ideas of the Flory lattice theoryand the UNIFAC group contribution method are employed to get the expression of themixing free energy. Then we deduce a particular model by combining this mixing freeenergy with the conservation laws equations and constitutive relations of both phasesto predict the volume transition behaviors of these special hydrogels.